Ultrafine Diesel Exhaust Particles Induce Apoptosis of Oligodendrocytes by Increasing Intracellular Reactive Oxygen Species through NADPH Oxidase Activation - Ji Young Kim; Jin-Hee Kim; Yong-Dae Kim; Je Hoon Seo (MDPI AG, 2022)
Diesel exhaust particles (DEPs) are a main contributor to air pollution. Ultrafine DEPs can cause neurodegenerative diseases by increasing intracellular reactive oxygen species (ROS). Compared with other cells in the brain, oligodendrocytes responsible for myelination are more susceptible to oxidative stress. However, the mechanisms underlying ROS generation in oligodendrocytes and the susceptibility of oligodendrocytes to ROS by ultrafine DEPs remain unclear. Herein, we examined the effects of excessive ROS generated by NOX2, an isoform of the NADPH oxidase family, after exposure to ultrafine DEPs (200 μg/mL) on the survival of two types of oligodendrocytes-oligodendrocyte precursor cells (OPCs) and mature oligodendrocytes (mOLs)--isolated from the brain of neonatal rats. In addition, mice were exposed to ultrafine DEP suspension (20 μL, 0.4 mg/mL) via the nasal route for 1 week, after which the expression of NOX2 and cleaved caspase-3 was examined in the white matter of the cerebellum. Exposure to DEPs significantly increased NOX2 expression and ROS generation in OPCs and mOLs. OPCs and mOLs clearly exhibited viability reduction, and a significant change in p53, Bax, Bcl-2, and cleaved caspase-3 expression, after DEP exposure. In contrast, treatment with berberine (BBR), an NOX2 inhibitor, significantly mitigated these effects. In mice exposed to DEP, the presence of NOX2-positive and cleaved caspase-3-positive oligodendrocytes was demonstrated in the cerebellar white matter; NOX2 and cleaved caspase-3 expression in the cerebellum lysates was significantly increased. BBR treatment returned expression of these proteins to control levels. These results demonstrate that the susceptibility of OPCs and mOLs to ultrafine DEPs is, at least in part, caused by excessive ROS produced by NOX2 and the sequential changes in the expression of p53, Bax, Bcl-2, and cleaved caspase-3. Overall, NOX2 inhibitor enhances the survival of two types of oligodendrocytes.